2017
DOI: 10.1007/s00429-017-1489-9
|View full text |Cite
|
Sign up to set email alerts
|

Localization of endogenous amyloid-β to the coeruleo-cortical pathway: consequences of noradrenergic depletion

Abstract: The locus coeruleus (LC)-norepinephrine (NE) system is an understudied circuit in the context of Alzheimer's disease (AD), and is thought to play an important role in neurodegenerative and neuropsychiatric diseases involving catecholamine neurotransmitters. Understanding the expression and distribution of the amyloid beta (Aβ) peptide, a primary component of AD, under basal conditions and under conditions of NE perturbation within the coeruleo-cortical pathway may be important for understanding its putative ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 77 publications
3
6
0
Order By: Relevance
“…Western blot analysis was conducted in parallel with ELISA studies to determine protein expression levels of the NE synthesizing enzyme, DβH, in these animals. These results were recently reported, and indicate that DβH protein expression in DSP-4-treated animals was significantly reduced compared to saline and naïve rats (Ross et al, 2017). It is possible that the effects of NE depletion on the eCB system in the PFC are indirect.…”
Section: Discussionsupporting
confidence: 83%
“…Western blot analysis was conducted in parallel with ELISA studies to determine protein expression levels of the NE synthesizing enzyme, DβH, in these animals. These results were recently reported, and indicate that DβH protein expression in DSP-4-treated animals was significantly reduced compared to saline and naïve rats (Ross et al, 2017). It is possible that the effects of NE depletion on the eCB system in the PFC are indirect.…”
Section: Discussionsupporting
confidence: 83%
“…Our laboratory is the first to have localized endogenous Aβ 42 peptides to LC neurons of the naïve rat in vivo using fluorescence microscopy and immunoelectron microscopy ( 248 ). Using highly sensitive ELISA for Aβ 42 , we demonstrated that NE and Aβ 42 levels positively correlate in the naïve rat.…”
Section: Modern Integrated Perspectives Of Arousal and The Lc-ne Systmentioning
confidence: 99%
“…As alluded to earlier, altered protein and activity have been reported in both PD and AD. This can occur in several ways such as degeneration of LC noradrenergic neurons, neuroinflammation, and dysregulation of copper levels that are all associated with both neurological diseases (McMillan et al ; Trillo et al ; He et al ; Tang et al ; Peterson and Li ; Ross et al ).…”
Section: Dβh In Neurodegenerative Diseasementioning
confidence: 99%